Effects and Mechanisms of Anti-CD44 Monoclonal Antibody A3D8 on Proliferation and Apoptosis of Sphere-Forming Cells With Stemness From Human Ovarian Cancer. Issue 8 (1st October 2013) - Du, Yong-Rui; Chen, Ying; Gao, Yan; Niu, Xiu-Long; Li, Ya-Jing; Deng, Wei-Min
Abstract : Objective: CD44 + human ovarian cancer stem cells (CSCs) and CSC-like cells have been identified and characterized. Compelling evidence has revealed that CD44 is involved in the occurrence and development of cancers. Our previous study showed that sphere-forming cells (SFCs) from the human ovarian cancer cell line SKOV-3 had CSC capacity. Therefore, in the present study, we aimed to investigate the effects and mechanisms of the anti-CD44 monoclonal antibody A3D8 on the proliferation and apoptosis of SFCs to explore novel strategies for the treatment of ovarian cancer. Methods: We investigated the effects and mechanisms of A3D8 on the proliferation and apoptosis of SFCs using the MTS assay, cell cycle analysis, an annexin V-fluorescein isothiocyanate/propidium iodide kit, Rh123 apoptosis detection kit, real-time reverse transcription polymerase chain reaction and Western blotting. Results: After CD44 ligation by A3D8, SFC cell proliferation was notably attenuated, cell cycle progression was arrested in the S phase, and apoptosis was significantly increased. The effect of A3D8 was enhanced in a dose- and time-dependent manner, and the effect of apoptosis induction by DDP was enhanced by combination treatment with A3D8. Furthermore, the messenger RNA expression levels of p21 and caspase-3 were up-regulated, whereas those of CDK2, cyclinA, and Bcl-2 were down-regulated. The protein expression levels of caspase-3 were up-regulated, whereas those of CDK2, cyclinA, and Bcl-2 were down-regulated. Conclusions: Our findings indicate that anti-CD44 monoclonal antibodies may be a potential strategy for the treatment of human ovarian cancer after conventional therapy via inhibition of growth and the promotion of apoptosis in SFCs with stemness.